Percepción de la adherencia a tratamientos en pacientes con factores de riesgo cardiovascular (2012)
ABSTRACT: To identify the perceptions regarding adherence to treatment among patients with cardiovascular risk undergoing pharmacological or non-pharmacological treatment. Methodology: A transversal study using the instrument “issues influencing adherence to pharmacological or non-pharmacological treatments in patients with cardiovascular risk factors". The study assesses four major factors in 256 adults living in Medellín (Colombia, South America), namely: socio-economic factors, factors related to the healthcare service provider, factors related to the therapy itself, and patient-related factors. Results: In terms of the perception of treatment adherence, socio-economic factors had the lowest score. Additionally, the educational level of patients was found to be the factor with the strongest influence on adherence perception. Discussion: This study approaches the various aspects of the issue of treatment adherence with more extensive knowledge in order to contribute to the development of strategies for improving treatment adherence in patients with cardiovascular risk. The study also suggests communicating medical recommendations in different manners and in a patient-friendly language (i.e. a kind of language with no technical words). Likewise, establishing more effective strategies for diet management is suggested.